(3cJGH GdCaYGds - (3Ydj Hf LYaQ Hf Ydj GdSYOj, CHh GdbGSe, GdSYOj GdUbdj GdeUQj, GdeYQha H GHf GdbWGY,J (B515 (3g` s; (3eMeO Hf YeQ Hf YHO GdYRjR Hf EHQGgje GdCfOdSj, CHhHcQ GHf GdbhWjg,J (B367 (3g` s ((3CMeO Hf EHQGgje Hf eMeO Hf EOQjS Hf HGHG Lhc s)
(3ChdgG (B:s
(3hGNdU dc eG YSQ eG fYJeO ef cJGH CHfjI GdCaYGd s
(3BNQgG (B:s
(3hdG GdNeGSi hdG GdSOGSi hGddg CYde s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3JgPjHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B311 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B84s
Keywords: (3GdUQas